On Marginal Returns and Inferior Inputs - Paolo Bertoletti; Giorgio Rampa (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2011)
A necessary and sufficient condition for an input to be inferior is that, taking into account the input adjustment, an increase of its price raises the marginal productivity of all inputs. Contrary to a widespread opinion, it is not necessary that (some) inputs are rivals (i.e., that some marginal productivity cross derivative is negative). We discuss these facts and illustrate them by introducing a few simple functional forms for the production function. Our results suggest that the existence of inferior inputs is naturally associate to the presence of increasing returns, and possibly make the case for inferiority considerably stronger.
Keywords: D11; D21; D24; 330; inferior and normal inputs; marginal productivity; homotheticity